On Temporary Keynesian Equilibria - Grandmont, Jean-Michel; Laroque, Guy (Review of Economic Studies, 1976)
Jean-Michel Grandmont, Guy Laroque; On Temporary Keynesian Equilibria, The Review of Economic Studies, Volume 43, Issue 1, 1 February 1976, Pages 53–67, ht